Industrial training report: Jabatan Penyiaran Kelantan (RTM) / Nurezian Syurana Mohamad - Mohamad, Nurezian Syurana (Perpustakaan Tengku Anis, 2019)
This report highlight about industrial training at Jabatan Penyiaran Kelantan (RTM). Industrial Training will be duration five month starting with 3 February 2019 until 30 June 2019. The trainee gets many tasks during industrial training and knowledge in real working. In duration internship the trainee involve activities in technical and also media conference. There are many activities that have been complete by trainee which is in editing the video, outside broadcasting, make a news coverage and PA system event. During industrial training, the trainees discuss with supervisor industrial training and faculty and decide to make a special project which is Sistem Aduan ICT dan M&E for Jabatan Penyiaran Kelantan. This system focused to staff RTM for complaint related in IT and maintenance only. Sistem Aduan will be conducted by admin which is ICT staff and maintenance staff. That person responsible to monitor complaint by user. Every department responsible to control and manage complaint by user in RTM Kelantan. This system very easy for using weather manual method before that. This is because user just need to register first and can be login in their system. Sistem Aduan suitable using by staff in R TM Kelantan.